(untitled) - Bradbury, Andrew (London, 2010)
Presentation skills are essential for business success and are needed in all sorts of business situations - guiding a new colleague through the basic office procedures, reporting back to a departmental meeting, any kind of sales call (by telephone or face-to-face), or giving the members of the board an overview of a new product. Successful Presentation Skills is packed with practical advice, addressing the common problems many people face when making a presentation. Ideal for the inexperienced speaker and anyone wanting to improve their communication skills, it includes tips on building confidence, understanding body language, and using visual aids effectively.
Keywords: Business presentations,Thuyết trình trong kinh doanh